Effect of Traditional and Modern Cooking Methods on the Microbial and Physicochemical Quality of Jollof Rice - Nnenna Jennifer Omorodion; Olanrewaju Olubukola E (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
Jollof rice is a popular West African dish, but its microbiological and physicochemical quality can be compromised by cooking methods. This study investigated the effect of traditional and modern cooking methods on the microbiological and physicochemical quality of Jollof rice sold around University of Port Harcourt. 20 samples of Jollof rice were collected from vendors, cooked using with firewood and gas cooker. Microbiological analysis and physicochemical analysis were conducted using standard methods. Microbiological analysis revealed that firewood cooked Jollof rice had higher total heterotrophic bacteria count (3.7×104 CFU/g to 4.5×104 CFU/g), exceeding stipulated standards. It was also observed that gas cooked Jollof rice had higher fungal count (1.4×103 CFU/g to 8×103 CFU/g) was within stipulated microbiological standard. Firewood-cooked Jollof rice had higher microbial counts compared to gas cooked Jollof rice. Five bacteria species: Bacillus subtilis, (18.75%); Klebsiella sp, (12.5%); Bacillus cereus, (18.75%); Staphylococcus aureus, (43.75%); and Proteus mirabilis, (6.25%) and three fungi species: Aspergillus niger, (57.1%); Fusarium sp, (14.3%) and Penicillum sp, (28.6%) were isolated. Physicochemical analysis showed that firewood cooked Jollof rice had higher values in; Ash, fibre, lipid and moisture content compared to gas-cooked Jollof rice. Gas-cooked Jollof rice had better physicochemical properties, including lower pH and higher protein content. This study concludes that Traditional cooking methods (firewood) may compromise the microbiological and physicochemical quality of Jollof rice, while modern methods (gas) produce safer and more nutritious products. This study highlights the importance of adopting safe cooking practices to ensure food safety and quality.